Type-of-service routing in datagram delivery systems. - Matta, I. (IEEE Journal on selected areas in communications)
The Internet is expected to support various services, including best-effort services and guaranteed services. For best-effort services, we propose a new approach to achieving type-of-service (TOS) classes with adaptive next-hop routing. We consider two TOS classes, namely, delay-sensitive and throughput-sensitive. As in routing protocols such as OSPF and integrated IS-IS, each node has a different next-hop for each destination and TOS class. Traditionally, a node has a single FCFS queue for each outgoing link, and the next-hops are computed using link measurements. In our approach, we attempt to isolate the two traffic classes by using for each outgoing link a separate FCFS queue for each TOS class; the link is shared cyclicly between its TOS queues. The next-hops for the delay-sensitive traffic adapts to link delays of that traffic. The next-hops for the throughput-sensitive traffic adapts to overall link utilizations. We compare our approach with the traditional approach using discrete-event simulation and Lyapunov analysis (for stability of routes). Our approach offers lower end-to-end delay to the delay-sensitive traffic. A related property is that the routes for the delay-sensitive traffic are more stable, i.e., less oscillations. An unexpected property is that the overall end-to-end delay is lower, because the throughput-sensitive traffic moves away to under-utilized routes